Highly facile Ag/NiO nanocomposite synthesized by sol-gel method for mineralization of rhodamine B - Pandey S.K.; Tripathi M.K.; Ramanathan V.; Mishra P.K.; Tiwary D. (My University, 2025)
A Ag/NiO nanocomposite photocatalyst was synthesized by sol-gel route without using any surfactant, and it was utilized for the mineralization of the organic pollutant rhodamine B (RhB) dye. The HR-TEM result confirms the formation of a close interface between Ag and NiO, the X-ray diffraction pattern also confirms the formation of Ag/NiO nanocomposite. UV–vis absorbance spectra of RhB ratified that modified NiO nanoparticles have higher photocatalytic mineralization efficiency (up to 97%) than undoped NiO under UV light and Ag doped NiO exhibited the utmost photocatalytic performance with the highest turnover frequency (TOF) up to date and followed pseudo-first-order kinetics. The recyclability measurement of the photocatalyst as well as the XRD results of the used catalyst confirms zero corrosion of the photocatalyst. The result of the photocatalytic experiments demonstrates that introduction of Ag with NiO restrains the process of charge recombination between photogenerated electrons/holes and consequently facilitates the mineralization of RhB dye. © 2021 Elsevier Ltd